1903 Utah Laws 155, ch. 116, § 24 - (:unkn) unknown (My University, 1903)
It shall be unlawful and a misdemeanor for any person to use any gun larger than ten gauge while hunting for fowl or birds."
Keywords: HUNTING REGULATION